2012
DOI: 10.1002/jmv.23244
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of drug resistance mutations in naïve and ART‐treated patients infected with HIV‐1 in Yaounde, Cameroon

Abstract: Currently the prevalence of HIV‐1 infection in Cameroon is 5.1%, CRF02_AG subtype is responsible for about 50% of infections. Since an HIV‐1 drug resistance test is not yet available widely, accurate data on the prevalence of resistant viral strains are missing. The objective of this study was to determine HIV‐1 genetic diversity and to characterize HIV‐1 mutations conferring drug resistance among antiretroviral therapy (ART)‐naïve and ART‐treated patients. A cohort of 239 patients infected with HIV were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
43
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 29 publications
(29 reference statements)
12
43
2
Order By: Relevance
“…These findings are consistent with previous studies that have reported similar rates of acquired drug resistance mutations in Cameroon (8,23) and other African countries with similar ART programs (10,31,32). The most prevalent mutations identified were M184V and K103N.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with previous studies that have reported similar rates of acquired drug resistance mutations in Cameroon (8,23) and other African countries with similar ART programs (10,31,32). The most prevalent mutations identified were M184V and K103N.…”
Section: Discussionsupporting
confidence: 93%
“…Among the ART-naive patients, 18% and 15% harbored viruses with NRTI-associated mutations (M184V and T215Y/F) and viruses with NNRTI-associated mutations (K103N and Y181C), respectively. These prevalence rates are higher than the rates seen in earlier studies in Cameroon, which reported transmitted drug resistance rates in Cameroon ranging from 1.9% to 12.3% (1,11,23) in ART-naive patients. This increasing rate of transmitted HIVDR mutation is consistent with the increase in the availability of ARV in Cameroon over time.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This level of drug adherence is very difficult to attain for PLH who are unable to sustain scheduled clinic follow-up visits, as studies indicate that the majority of patients with LTFU stop their ART. Stopping ART has been reported to quickly increase the risk of developing high serum viral load and other adverse health consequences [2, 5, 8, 9] including ART drug resistance, progression of HIV to AIDS, premature mortality, and re-infection, or infection of others with resistant strains [24, 10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…Cameroon is located in west central Africa, the epicentre of the HIV epidemic, where many HIV-1 types and subtypes co-circulate Tebit and Arts, 2011). Despite having a relatively low HIV prevalence, Cameroon has one of the most genetically diverse HIV epidemics in the world, with a very large variety of HIV-1 circulating recombinant forms (CRFs) Carr et al, 2010;Ceccarelli et al, 2012;Soares et al, 2010;Tongo et al, 2013;Torimiro et al, 2009). Subtypes CRF02_AG and G are among the most prevalent HIV-1 group M (HIV-1M) lineages in Cameroon Tongo et al, 2013) and in west Africa in general (Hemelaar et al, 2011).…”
Section: Introductionmentioning
confidence: 95%